Improving the reliability of Schottky diodes under the influence of electrostatic discharges - Sоlоdukha, V. A.; Turtsevich, A. S.; Solov’yov, J. A.; Rubtsevich, I. I.; Kerentsev, A. F. (Technology and design in electronic equipment, 2012)
Experimental studies of Schottky diodes with molybdenum barrier structure showed that resistance of the structures to electrostatic discharge depends on the design parameters, as well as on guard ring diffusion depth. It has been proven that to improve the reliability of Schottky diodes one should use the structures with distributed guard ring containing p-type cell matrix. This reduces the electric field strength in critical areas of the active structure due to potential balancing along the guard ring and the diode area perimeter.